Answer:
[tex]-2,\ -1,\ -\dfrac{1}{2},\ 3.[/tex]
Step-by-step explanation:
Consider polynomial [tex]2x^4+x^3-14x^2-19x-6.[/tex]
If x=-2 is its zero, then you can divide the polynomial [tex]2x^4+x^3-14x^2-19x-6[/tex] by [tex]x+2[/tex] and get
[tex]2x^4+x^3-14x^2-19x-6=(x+2)(2x^3-3x^2-8x-3).[/tex]
If x=-1, then the polynomial [tex]2x^4+x^3-14x^2-19x-6[/tex] can be rewritten as
[tex]2x^4+x^3-14x^2-19x-6=(x+2)(x+1)(2x^2-5x-3).[/tex]
The quadratic polynomial has roots
[tex]x_{1,2}=\dfrac{-(-5)\pm\sqrt{(-5)^2-4\cdot2\cdot(-3)}}{2\cdot 2}=\dfrac{5\pm \sqrt{25+24}}{4}=\dfrac{5\pm \sqrt{49}}{4}=3,-\dfrac{1}{2}.[/tex]
Then the polynomial [tex]2x^4+x^3-14x^2-19x-6[/tex] has zeros [tex]-2,\ -1,\ -\dfrac{1}{2},\ 3.[/tex]